2021
DOI: 10.1038/s41598-021-00986-0
|View full text |Cite
|
Sign up to set email alerts
|

Salt inducible kinases 2 and 3 are required for thymic T cell development

Abstract: Salt Inducible Kinases (SIKs), of which there are 3 isoforms, are established to play roles in innate immunity, metabolic control and neuronal function, but their role in adaptive immunity is unknown. To address this gap, we used a combination of SIK knockout and kinase-inactive knock-in mice. The combined loss of SIK1 and SIK2 activity did not block T cell development. Conditional knockout of SIK3 in haemopoietic cells, driven by a Vav-iCre transgene, resulted in a moderate reduction in the numbers of periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that SIK3 is a target of regulating innate immunity 2,13 . Furthermore the absence of SIK2/3 can inhibit the progression to mature single positive T cells 31 . However, the independent effects of SIK2 on immune injury and the maturation of T cells and B cells were not explored before.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that SIK3 is a target of regulating innate immunity 2,13 . Furthermore the absence of SIK2/3 can inhibit the progression to mature single positive T cells 31 . However, the independent effects of SIK2 on immune injury and the maturation of T cells and B cells were not explored before.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore have been of interest to examine SIK2/3 double knockin mice; however, this was not possible as loss of both SIK2 and SIK3 activity results in embryonic lethality ( 33 ). Furthermore, although mice with a double knockout of both SIK2 and SIK3 in the immune system are viable, they exhibit a failure of thymic T-cell development and very low numbers of peripheral T cells ( 65 ), which would make interpreting the results of bleomycin-induced fibrosis problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the LOUCY acute lymphoblastic leukemia cell line with HG-9-91-01 restored normal T-cell development ( 247 ), therefore suggesting that the SIKs impact lymphoid lineage decision-making via regulating MEF2C activity. Indeed, utilizing a combination of SIK KO and SIK KI mice, Nefla et al ( 248 ) demonstrated that SIK2 and SIK3 are critical regulators of in vivo T-cell development. While SIK2 KI or SIK1/2 double KI mutants had normal T- and B-cell compartments, SIK3 floxed/Vav-iCre animals (where SIK3 is genetically deleted only in hematopoietic cells) displayed slightly reduced T-cell numbers in the spleen and lymph nodes, while B-cell numbers remained unaffected ( 248 ).…”
Section: The Physiological Roles Of Salt-inducible Kinasesmentioning
confidence: 99%
“…Indeed, utilizing a combination of SIK KO and SIK KI mice, Nefla et al ( 248 ) demonstrated that SIK2 and SIK3 are critical regulators of in vivo T-cell development. While SIK2 KI or SIK1/2 double KI mutants had normal T- and B-cell compartments, SIK3 floxed/Vav-iCre animals (where SIK3 is genetically deleted only in hematopoietic cells) displayed slightly reduced T-cell numbers in the spleen and lymph nodes, while B-cell numbers remained unaffected ( 248 ). Furthermore, SIK2 KO/SIK3 floxed/Vav-iCre double mutant animals had normal peripheral B-cell numbers but drastically reduced T-cell counts in the thymus, spleen, and lymph nodes, with most of any remaining cells displaying an immature phenotype ( 248 ).…”
Section: The Physiological Roles Of Salt-inducible Kinasesmentioning
confidence: 99%